THE INFLUENCE OF PERSONALITY AND SCHOOL ENVIRONMENT ON STUDENTS’ MORAL: A REVIEW ON INTERNATIONAL SCHOOL USING CONVERGENCE THEORY - Nur Fiezila Mohd Rezaly; Hishamuddin Ahmad; Nor Hasnida Che Md Ghazali (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Moral formation begins with the personality of the individual and the environmental factors around the individual. Consequently, an individual’s propensity to be good or bad depends on internal and external factors that motivate him or her to act through his or her conduct. It is necessary to create a situation that may lead to the application of good moral values to students by a conducive education. This can ensure a motivated generation committed to fulfilling their responsibilities to themselves, their families, their peers, society and the country. This study uses Convergence Theory to examine the extent of the influence of personality and school environment in shaping the morals of Malaysian students who attend international schools in the Klang Valley.